Experimental realization of stimulated Raman shortcut-to-adiabatic passage with cold atoms - Yan-Xiong Du (Nature Portfolio, 2016)
Stimulated Raman adiabatic passage is a robust approach to realize high-fidelity state transfer, but requires long operation. Here, the authors propose a shortcut-to-adiabatic protocol to speed up such approach by modifying the Raman pulses, and demonstrate it in a cold atomic setup.